Ego psychology of depression with implications for treatment - Rosen, Irving M. (1970)
Concepts suggested by autonomous ego theory and a phenomenological approach to emotions make it possible to think again about depression and its treatment in order better to explain clinical observations.Depression appears to be a secondary emotion, not primary, made up of the following ingredients: 1) one or more primary emotionsanxiety, anger, guilt, and grief particularly, as well as self-pity, loneliness, alienation, apathy, and despairprecipitated in 2) an ego inadequate in channeling emotions constructively, 3) the associated phenomenological tendencies inherent within the emotions, and 4) the sense of helplessness that ensues. Thus the treatment required would consist of a systematic, somewhat detached, cognitive approach to the problems the emotions are indicating, and what should be done to resolve them. These problems include those precipitated by the workings of the emotions as things-in-themselves. The treatment is oriented toward enhancing the patient's understanding of the disorder and his coping ability to the end that the patient is not weakened even as he is relieved.
Keywords: Clinical Observation; Cognitive Approach; Coping Ability; Phenomenological Approach; Primary Emotion